Eastern and North Eastern sub-divisions of India : An analysis of trend and chaotic behaviour of rainfall in different seasons - PIJUSH, BASAK (MAUSAM, 2020)
The aim of the study is to understand trend or non-linearity along with a chaotic behaviour, if any, of Eastern and North Eastern sub-divisional rainfall, namely Orissa, Gangetic West Bengal, Sub Himalayan West Bengal, Assam and Meghalaya and also Nagaland, Manipur, Mizoram and Tripura based on rainfall data of 143 years (1871-2013). The analysis is performed for examining behaviour of rainfall in each of the seasons, namely, Pre monsoon, South West monsoon, North East monsoon and also Annual rainfall extracted from the monthly data. For that purpose, a trend analysis with Hurst Exponent and non-linearity analysis with Lyapunov Exponent are employed. The analysis revealed that rainfall of Orissa is persistent for all the seasons whilst the rainfall is persistent in Gangetic West Bengal in Pre monsoon and North East monsoon and Assam and Meghalaya along with Nagaland, Manipur, Mizoram and Tripura exhibit persistent behaviour in South West Monsoon and annually. Sub Himalayan West Bengal exhibit persistence in annual rainfall only. Chaotic tendency in low magnitude is located in many cases whilst non-chaotic situation has occurred when the persistence is found, mainly in pre-monsoon season. Moreover, the analysis of Hurst and Lyapunov Exponent revealed to identify two groups of sub-divisions with exactly similar region of every respect. Those two groups contain (i) sub-divisions Orissa and Assam and Meghalaya and also (ii) sub-divisions Sub Himalayan West Bengal and Nagaland, Mizoram, Manipur and Tripura although those are at distances of hundreds of kilometers away. The behaviour of those subdivisions in a group has similar behaviour in all respects.